Ebstein's Anomaly: "The One and a Half Ventricle Heart" - Malhotra,Amber (2018)
Abstract Objective: Ebstein's anomaly remains a relatively ignored disease. Lying in the 'No Man's land' between congenital and valve surgeons, it largely remains inadequately studied. We report our short-term results of treating it as a 'one and a half ventricle heart' and propose that the true tricuspid annulus (TTA) 'Z' score be used as an objective criterion for estimation of 'functional' right ventricle (RV). Methods: 22 consecutive patients undergoing surgery for Ebstein's anomaly were studied. Echocardiography was performed to assess the type and severity of the disease, tricuspid annular dimension and its 'Z' score. Patients were operated by a modification of the cone repair, with addition of annuloplasty, bidirectional cavopulmonary shunt (BCPS) and right reduction atrioplasty to provide a comprehensive repair. TTA 'Z' score was correlated later with postplication indexed residual RV volume. Results: There was one (4.5%) early and no late postoperative death. There was a significant reduction in tricuspid regurgitation grading (3.40±0.65 to 1.22±0.42, P<0.001). Residual RV volume reduced to 71.96±3.8% of the expected volume and there was a significant negative correlation (rho −0.83) between TTA 'Z' score and indexed residual RV volume. During the follow-up of 20.54±7.62 months, the functional class improved from 2.59±0.7 to 1.34±0.52 (P<0.001). Conclusion: In Ebstein's anomaly, a higher TTA 'Z' score correlates with a lower postplication indexed residual RV volume. Hence, a complete trileaflet repair with offloading of RV by BCPS (when the TTA 'Z' score is >2) is recommended. The short-term outcomes of our technique are promising.